Performance differences between aphasia and healthy aging on an executive function test battery. - Mohapatra, Bijoyaa; Marshall, Rebecca Shisler (International Journal of Speech-Language Pathology, 2020)
Purpose: Executive function (EF) deficits commonly co-occur with other linguistic and non-linguistic deficits in aphasia. The questions about whether, and to what extent, people with aphasia (PWA) present deficits on different executive functions (EFs) is relatively understudied. Method: In this study, four EFs, set-switching, updating, inhibition, and dual task processing were evaluated in aphasia and healthy groups. Three groups of participants: 30 healthy young, 30 healthy old, and 10 PWA were assessed on four tasks, Colour Trails Test (CTT 1 and 2), Conners' Continuous Performance Test II (CPT II), n-back (1- and 2-back), and divided attention task that tapped into different EFs. In order to examine performance differences on the EF tasks between the participant groups, repeated measures and multivariate analysis of variances with follow-up pairwise comparisons were computed. Pearson product-moment correlations were conducted to evaluate the strength and direction of the association between aphasia severity (on Western Aphasia Battery-Revised) and executive functioning. Result: PWA demonstrated significantly diminished performance on all EF tasks in comparison to healthy groups and differences were distinct on the higher-level complexity tasks such as the 2-back and CTT 2. The healthy older group demonstrated elevated response times on the CTT, CPT II, and divided attention tasks, and decreased sensitivity scores on the CPT II and n-back in comparison to the younger group. Also, aphasia severity correlated with reduced performance on selective EF measures. Conclusion: This study emphasises the importance of investigating EF deficits in PWA and its potential relationship to language behaviour. Understanding EF is critical for comprehension of linguistic and non-linguistic deficits and in planning treatment for PWA.